Subversion of the actin cytoskeleton during viral infection - Taylor, Matthew P.; Koyuncu, Orkide O.; Enquist, Lynn W. (Nature reviews. Microbiology, 2011)
Key Points Actin is a ubiquitous cellular protein that forms a foundation for cellular structure and integrity. Viruses are obligate intracellular parasites with a replication cycle that requires them to engage and modify the actin cytoskeleton at all stages, from entry through replication to egress and spread. Oncogenic proteins of transforming viruses interfere with the RHO-family GTPases (actin-signalling molecules) to change cellular dynamics from a quiescent to a mitotic state. The actin cytoskeleton is altered dramatically, cell shape changes, and cell-to-cell contact and matrix adhesion are lost, while podosomes and membrane ruffles appear on the cell surface. Virus-mediated oncogenic transformation can result in metastatic tumours in humans, such as nasopharyngeal, hepatocellular and cervical carcinomas (induced by Epstein–Barr virus, hepatitis B virus and human papillomavirus, respectively). In vitro, viral proteins increase cell migration by disrupting and modulating actin dynamics. The host proteins involved in these interactions may be specific cytoskeletal targets for antimetastatic therapies. Virions often interact with the underlying actin cytoskeleton to gain entry to the cell. Virions may move to entry sites using high-affinity interactions with receptors that are associated with actin filaments inside the cell. Movement is promoted by myosin motors that drive the actin cytoskeleton, pulling the receptor–virion complex across the plasma membrane. Virion entry by endocytic processes or formation of the fusion pore also often involves cortical actin. Actin structures can be modified during viral infection to produce long cellular extensions (for example, filopodia and tunnelling nanotubes). These structures facilitate the long-distance dissemination of a wide range of viruses, including vaccinia virus, herpes simplex viruses, HIV and rotaviruses. Most actin–virus interactions have been discovered in isolated or cultured cell systems. The next generation of research will apply this knowledge to viral infections in vivo to understand the role of viral subversion of the actin cytoskeleton in disease. Manipulation of the host cell actin cytoskeleton is a common feature for many viruses. In this Review, Taylor, Koyuncu and Enquist describe how the interaction of viral proteins with the actin cytoskeleton alters the structure and function of this cytoskeleton, allowing viral infections to initiate, persist and spread. Viral infection converts the normal functions of a cell to optimize viral replication and virion production. One striking observation of this conversion is the reconfiguration and reorganization of cellular actin, affecting every stage of the viral life cycle, from entry through assembly to egress. The extent and degree of cytoskeletal reorganization varies among different viral infections, suggesting the evolution of myriad viral strategies. In this Review, we describe how the interaction of viral proteins with the cell modulates the structure and function of the actin cytoskeleton to initiate, sustain and spread infections. The molecular biology of such interactions continues to engage virologists in their quest to understand viral replication and informs cell biologists about the role of the cytoskeleton in the uninfected cell.